Academic bullying and human rights: is tt time to take them seriously? - Kostakopoulou, Theodora (Human rights review, 2024)
Notwithstanding universities’ many laudable aims, incidents of serious bullying, academic harassment and sexual harassment in academic settings are reported with increasing regularity globally. However, the human rights violations involved in bullying and academic harassment have not received attention by the literature. In this article, we pierce the veil of silence surrounding university environments and provide a systematic account of the breaches of international and European human rights law involved in academic bullying and harassment. By adopting a socio-legal lens, we shed light onto such practices and tactics, the breaches of specific human rights and norms and the reluctance of states and regulators to intervene in what is perceived to be universities’ ‘sovereign’ sphere of jurisdiction in order to prevent human rights’ violations and to protect the victims of human rights abuse. We call for a multi-faceted and multi-agency approach to tackle academic bullying and harassment, and make a number of institutional and policy recommendations to ensure universities’ compliance with human rights standards and the effective protection of academics under attack.